Prácticas contables y tributarias que adoptan los pequeños negocios en Colombia (2019)
This paper aims to describe accounting and tax practices of small companies in Colombia. In the other hand, describes the main matters faced by small business whose because of it's structure, tend to be linked with “informal market” taking into account that this sector has been defined as those who realize many activities legally exclude or out of the taxable field. In that order of ideas, grocery stores are known as business operating on a low scale, wich are integrated for employees working independently, also in most of cases, hire friends or family members in an informal way. From the theoretical component, research is supported by the Stakeholder theory proposed by Freeman, which establishes that organizations generate externalities to the communities in which they are immersed, from a biunivocal relationship, since communities also they make organizations configure themselves around their needs. From the methodological aspect, the research is mixed positivist with a descriptive approach and simple random sampling has been used as a strategy for the selection of the sample. After analyzing the information, it is concluded that formal accounting and tax practices in the population under study are almost nil, and the cause of this problem is the lack of knowledge in accounting, finance and taxation they have, as well as the insufficient mechanisms of control and support of government agencies to this population.